Fabrication & properties of aluminium-aluminium oxide (Al/Al2o3) composite material - Nasrah, Mohd Azmi (2016)
A composite is a material come from two or more material with different chemical properties. Metal matrix composites have a metal matrix and the fiber includes carbon and silicon carbide. In composites if the matrix is metal it is termed metal matrix composites. In this project, the metal matrix used is aluminium and the fiber material is aluminium oxide. The main objective of this project is to study the behavior of Al-Al2O3 composite in different volume fraction under various sintering temperature. In this project used powder metallurgy method. The steps of this method are mixing, compaction and sintering. Firstly, the mixing begin with prepar ing powder which is various in weight percentage 95% Al + 5% Al2O3, 90% Al + 10% Al2O3 and 85% Al + 15% Al2O3. Secondly, the mixed powders were pressed through compaction process by using the hydraulic press machine with 20 ton compaction load. Lastly, sintered in a furnace with different sintering temperature which is 500°C, 550°C and 580°C. The specimens are characterized and the microstructures of the composites were studied by using the optical microscope. Besides, the hardness was studied by using Vickers Micro Hardness testing machine. The different ceramic composition with different sintering temperature influences in the Al-Al2O3 composite material and affect the density before and after sintering process, hardness test and microstructure in Al-Al2O3 composite material.